Ultra-Low-Dose Pre-Metallation Strategy Served for Commercial Metal-Ion Capacitors - Song, Zirui; Zhang, Guiyu; Deng, Xinglan; Zou, Kangyu; Xiao, Xuhuan; Momen, Roya; Massoudi, Abouzar; Deng, Wentao; Hu, Jiugang; Hou, Hongshuai; Zou, Guoqiang; Ji, Xiaobo (Nano-Micro Letters, 2022)
Sacrificial pre-metallation strategy could compensate for the irreversible consumption of metal ions and reduce the potential of anode, thereby elevating the cycle performance as well as open-circuit voltage for full metal ion capacitors (MICs). However, suffered from massive-dosage abuse, exorbitant decomposition potential, and side effects of decomposition residue, the wide application of sacrificial approach was restricted. Herein, assisted with density functional theory calculations, strongly coupled interface (M–O–C, M = Li/Na/K) and electron donating group have been put forward to regulate the band gap and highest occupied molecular orbital level of metal oxalate (M2C2O4), reducing polarization phenomenon and Gibbs free energy required for decomposition, which eventually decrease the practical decomposition potential from 4.50 to 3.95 V. Remarkably, full sodium ion capacitors constituted of commercial materials (activated carbon//hard carbon) could deliver a prominent energy density of 118.2 Wh kg−1 as well as excellent cycle stability under an ultra-low dosage pre-sodiation reagent of 15–30 wt% (far less than currently 100 wt%). Noteworthily, decomposition mechanism of sacrificial compound and the relative influence on the system of MICs after pre-metallation were initially revealed by in situ differential electrochemical mass spectrometry, offering in-depth insights for comprehending the function of cathode additives. In addition, this breakthrough has been successfully utilized in high performance lithium/potassium ion capacitors with Li2C2O4/K2C2O4 as pre-metallation reagent, which will convincingly promote the commercialization of MICs. Highlights: 1 Interfacial bonding strategy has been successfully applied to address the high overpotential issue of sacrificial additives, which reduced the decompositon potential of Na2C2O4 from 4.50 to 3.95 V. 2 Ultra-low-dose technique assisted commercial sodium ion capacitor (AC//HC) could deliver a remarkable energy density of 118.2 Wh kg−1 as well as excellent cycle stability. 3 In-depth decomposition mechanism of sacrificial compound and the relative influence after pre-metallation were revealed by advanced in situ and ex situ characterization approaches.